Additional considerations for the introduction to the dosier “Music journalism in Latin America: cultural processes and interdisciplinarity” (Revista Argentina de Musicología, 2026)
Introduction to the dosier
Keywords: music and press; nationalism; modernism; avant-garde; music and cinematography